2016
DOI: 10.1080/19476337.2016.1243587
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of Moringa oleifera L. and Bidens pilosa L. leaf extracts and their effects on oxidative stability of ground raw beef during refrigeration storage

Abstract: The study examined the leaf extracts of Moringa oleifera and Bidens pilosa for presence of bioactive phytochemicals and their antioxidant activities on pH and lipid oxidation of fresh ground beef during 6 days cold storage. The results revealed that B. pilosa leaf extract contained higher amount of bioactive compounds and antioxidant contents (p < 0.05) than M. oleifera leaf extract. The extract of B. pilosa leaf exhibited higher antiradical activity against 2,2-Diphenyl-2-picrylhydrazyl and 2,2íazino-bis-3-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 31 publications
8
37
1
1
Order By: Relevance
“…In addition to these phytoconstituents, the prevalence of fatty acids and fatty acid esters also aid to a significant increase in the antioxidant potential of H. sabdariffa in S. cerevisiae system which is reported for the first time (Sudha et al 2013;Sharma et al 2015). In the present study, C. caudatus leaf extract also exhibited significant antioxidant activity due to presence of substantial amount of phytol and hexamethyl cyclotrisiloxane as evident from the GC-MS analysis (Shibula and Velavan 2015;Falowo et al 2016).…”
Section: Gc-ms Analysissupporting
confidence: 59%
“…In addition to these phytoconstituents, the prevalence of fatty acids and fatty acid esters also aid to a significant increase in the antioxidant potential of H. sabdariffa in S. cerevisiae system which is reported for the first time (Sudha et al 2013;Sharma et al 2015). In the present study, C. caudatus leaf extract also exhibited significant antioxidant activity due to presence of substantial amount of phytol and hexamethyl cyclotrisiloxane as evident from the GC-MS analysis (Shibula and Velavan 2015;Falowo et al 2016).…”
Section: Gc-ms Analysissupporting
confidence: 59%
“…The result showed that the treated chicken meat had a lower value of DPPH in aerobic packaging, while a higher value of DPPH was found in untreated (control) samples. [54] reported that the extract of Bidenspilosa leaf exhibited higher antiradical activity against 2,2-diphenyl-2-picrylhydrazyl (DPPH) and radicals of 2,2íazinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) than Moringaoleifera leaf extract and standard butylated hydroxy toluene (BHT) fresh ground beef during 6 days of cold storage. In the DPPH assay, the highest antioxidant activities (expressed as μ mol TE/g) were observed for S. aromaticum (8.19 ± 0.12) and C. cassia (6.36 ± 0.17) extracts, followed by B. nigra (4.80 ± 0.12) and O. vulgare (3.30 ± 0.09) in raw chicken meat.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…Several researchers have demonstrated the efficacy of various natural antioxidants and antimicrobial agents with the potential to reduce lipid oxidation, spoilage and microbial load in meat and meat products ( Falowo et al., 2017 ; Ergezer et al., 2018 ). In addition, plant extracts have demonstrated activity against food-borne and pathogenic bacteria, including Bacillus cereus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella Typhimurium and Staphylococcus aureus ( Mostafa et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%